Infusing Pragmatism to Exploring Rationale behind Social Subjugation and Political Marginalization of Women in Pakistan - Rafeeq, Rifat; Khan, Abdul Basit (Annals of Human and Social Sciences, 2024)
The entrenched patriarchal attitudes within political parties and social fabric of Pakistan continue to view women as secondary political actors which fact is also reflected in the reluctance of political parties to nominate women for general seats or leadership roles within party hierarchies. Moreover, women are often seen as less viable candidates for competitive elections, and their political careers are frequently constrained by societal expectations that prioritize their domestic roles over their public and political ambitions. Although a substantial amount of scholarly work is devoted to political quotas and women representation across the world, research focusing on the qualitative analysis of these women in legislative positions, and the nature, scope and difficulties they experience within a male-dominated political system is rather scarce. In that perspective, the current study endeavors to focus on enhancing governance and strengthening the functional democracy in Pakistan particularly with reference to women’s representation in the National Assembly. This study seeks to fill the research gap in that dimension by adopting a qualitative research approach that enables one to understand the various aspects of transformation of gender based numerical representation of female politicians into substantive political power. The recommendations of the current study would help in future policy formulation and devising interventionist strategies for attaining gender equity as a foundation of political development.